Tingkat Kesulitan Adaptif pada Android Game bertema Flora Fauna Endemik Indonesia dengan Fuzzy Logic - Ahmad Rizal; Yani Parti Astuti; Abas Setiawan (Jurnal Buana Informatika, 2022)
Abstract. Adaptive Difficulty Level on Android of Indonesian Endemic Plants and Animals with Fuzzy Logic. The education of protecting endemic plants and animals in Indonesia requires the raising public awareness. One attempt is to develop an interactive digital games application. However, not all games are interesting to play. High boredom and frustration zones are also caused by the game content and level repetition that are not suitable for children's playing level. In this study, an Android-based educational game with theme Indonesian endemic plants and animals has been created with an adaptive level of difficulty according to the player's ability. The game mechanism is card gameslike with artificial intelligence using Sugeno Fuzzy logic which can automatically estimate the game level by drawing the card type at the game according to the player's ability. The results show that Sugeno Fuzzy made 35 correct decisions and 15 false decisions from 50 trials. Keywords: animals and plants, game, adaptive difficulty, fuzzy, testing Abstrak. Edukasi untuk melindungi flora dan fauna endemik di Indonesia diperlukan untuk menumbuhkan kesadaran bagi masyarakat. Salah satunya dengan aplikasi dari game digital yang interaktif. Namun, tidak semua game menarik untuk dimainkan. Zona bosan dan zona frustasi yang tinggi juga disebabkan karena pengulangan kasus dan tingkat permainan yang kurang sesuai dengan kemampuan bermain anak-anak. Pada penelitian ini diciptakan suatu game edukasi berbasis Android bertema flora dan fauna endemik Indonesia dengan tingkat kesulitan yang adaptif sesuai kemampuan pemain. Mekanisme game yang dibuat seperti game kartu dengan kecerdasan buatan menggunakan logika Fuzzy Sugeno yang mampu mempertimbangkan langsung tingkat permainan dengan cara mengeluarkan jenis kartu dalam lapangan permainan yang sesuai dengan kemampuan pemain. Hasil pengujian memperlihatkan Fuzzy Sugeno dapat membuat 35 keputusan dan 15 nilai pasti dari 50 kali percobaan. Kata Kunci: flora dan fauna, game, tingkat kesulitan adaptif, fuzzy, pengujian